Factors influencing the adoption of anglicisms. A study of juggling terminology - Kowalewski, Hubert (Papers in Linguistics, 2020)
The aim of the article is to determine the factors influencing the adoption of lexical borrowings from English into the terminology of Polish jugglers. Faced with the temptation to adopt an English term, users may resort to one of three main strategies: they may try to find or coin a Polish equivalent and use the equivalent exclusively, they may use the anglicism and the Polish equivalent interchangeably, or they may use the anglicism exclusively. The choice of the strategy is motivated mainly by: 1) the availability of the Polish equivalent, 2) syntactic and morphological simplicity of the borrowing and the Polish equivalent, 3) the degree of entrenchment of the Polish equivalent; 3) the degree of specialization the anglicism. In general, users tend to prefer simpler, more entrenched, and more specialized terms.